Study of the electromagnetic field and interpretation of magnetotelluric data in Vietnam - (:unkn) unknown (My University, 2011)
This thesis is devoted to the study of the electrical structure of the Earth's crust in two regions of Vietnam (the Red River Delta in the north and the region of the Saigon River fault in the south) and in West Africa. The data were those acquired during the International Year of the Equatorial Electrojet (IYEE). The technique used is the magnetotelluric (MT) sounding method. Two of the regions studied (southern Vietnam and West Africa) are located near the magnetic equator. Due to the presence of the equatorial electrojet in these regions, the assumption of plane wave, on which MT relies, is valid for a limited range of periods. Modeling of the induction by a Gaussian electrojet allowed us to characterize the source effect associated with the equatorial electrojet, and to determine for each studied region the period ranges for which the source effect is negligible. We have also shown that the source effect associated with the equatorial electrojet depends on the main features of the electrical structure of the basement, and the distance between the center of the equatorial electrojet and the location of the considered station. In the Red River Delta at the north, the MT profile is oriented SW-NE. It is about 32 km long, and goes across the major faults of the Red River fault system. MT data were applied 2-D inversion to obtain a electrical cross-section for the first three kilometers of the crust. This electrical cross-section, a density cross-section obtained by modeling of gravity data collected along the same profile, and information derived from holes drilled in the vicinity of the profile, both were used to construct a geological section of the study area. In the region of the Saigon River fault, the magnetotelluric profile is about 15 km long. It goes across the supposed location of the fault. The electrical structure of the first three kilometers of the crust was determined by 2-D inversion of data for periods which are not affected by the equ
Keywords: African Research